Subjective Well-Being and Security - Webb, Dave.; Webb, Dave.; Wills-Herrera, Eduardo.; Wills-Herrera, Eduardo. (Social Indicators Research Series, 2012)
In an era of greater globalization and development and employment of new technologies, many important security issues are being debated. Of significant concern is how security, or the perceived lack thereof, impacts on quality of life at multiple levels. These include questions raised concerning individual safety and security, organizational security, national security and so forth. In this context, an important consideration is how security should be best understood. Although definitions of how to understand human security have been proposed in the literature, it is not clear how security should be assessed. Security can be discussed from different perspectives and levels of analysis i.e., personal security, community security, economic security, food security, health security, political security, cyber security and so on. To tackle key questions related to the above, the editors have invited a number of noted international scholars from diverse fields of enquiry and representing different countries, to submit a chapter addressing key issues relevant to subjective well-being (SWB) and security from different disciplinary and interdisciplinary approaches. Considered together, the contents of this volume represent a timely and significant contribution to the knowledge bank of academics, practitioners, researchers and policy makers with an interest in this area. This book is aimed at well-being researchers, policy makers and think-tank participants as well as those involved in the industry of enforcement practice and research. The pages of the text are rich with best practice ideas that will be appropriate to any individual or organization with an interest in security provision from the micro to the meso level. .